TWO NEW Aphelenchoides Fischer 1894 (Nematoda: Tylenchina) FROM MANIPUR, NORTH EAST INDIA - Loukrakpam Bina Chanu; Naorem Mohilal (SEAMEO BIOTROP, 2014)
Two new species of Aphelenchoides discovered from different localities of Manipur, North East India had been described in the present study. Aphelenchoides longistylus sp. nov. has a long stylet and four lateral lines which are gradually merged into two at the tail region. Aphelenchoides neominoris sp. nov. has a small body and short tail with a stylet length of 8.6 Âµm.